118k views
4 votes
Choose the expression that represents the indicated composition. f(x) = 10x g(x) = x −3 (f º g)(x) = ? 10x – 30 10x – 3 10x2 – 30 10x2 – 30x

2 Answers

4 votes
(fºg)(x)=f(g(x))=f(x-3)=10(x-3)=10x-30
User Leppert
by
5.9k points
2 votes

Answer:

Option 1 -
(fog)(x)=10x-30

Explanation:

Given :
f(x)=10x and
g(x)=x-3

To find : Choose the expression that represents the indicated composition
(fog)(x)

Solution :

We know that,


(fog)(x)=f(g(x))

i.e.
(fog)(x)=f(x-3)


(fog)(x)=10(x-3)


(fog)(x)=10x-30

Therefore, Option 1 is correct.

User Ricalsin
by
6.5k points